Involvement of intracellular calcium and src tyrosine-kinase in capacitation of cryopreserved bovine spermatozoa - Satorre, M. (2010)
Increase of intracellular calcium concentration and tyrosine kinase involvement are pivotal in sperm capacitation. The aim was to determine the involvement of intracellular calcium and tyrosine kinases activity in frozen-thawed spermatozoa capacitated with heparin or quercetin. Genistein or PP2 (4-amino 5-(4-chlorophenyl)-7-(t-butyl)pyrazolo3,4, pyrimidine) were used to inhibit tyrosine kinases, and methoxyverapamil to inhibit voltage dependent calcium channels. Capacitation was determined by chlortetracycline and calcium by fluorescence spectrophotometry. Protein tyrosine-phosphorylation was determined by western blot. Pooled frozen semen samples from four bulls were used. In presence of heparin or quercetin capacitated spermatozoa percentage and intracellular calcium were greater (P<0.05) than in controls. Genistein, or PP2 addition in heparin treated samples decreased (P<0.05) capacitation and calcium, but not in quercetin treated samples. A differential inhibition of protein phosphorylation pattern was observed in heparin or quercetin treated suspension in presence of genistein or PP2. Methoxyverapamil blocked calcium increase in heparin, but not in quercetin treated samples. Capacitated spermatozoa percentage and calcium increase were similar with both inductors suggesting that they are capable to provoke capacitation by different mechanisms that dependent or not dependent on voltage dependent calcium channels, thus different intracellular compartments may be involved. In cryopreserved bovine spermatozoa tyrosine kinases including SRC-isoform modulate capacitation.